Components of Quantitative Resistance to Philippine Downy Mildew In Maize - D. Ruswandi; A. D. Raymundo; R. M. Lantican; D. M. Hautea; A. M. Salazar; A. L. Carpena (Zuriat, 2002)
Resistance to Philippine downy mildew (Peronosclerospora philippinensis) was observed in a BC1F2 population developed from a cross between the susceptible inbred line Pi 23 and the resistant inbred line P 345. Five components of resistance namely, disease incidence, disease severity, onset of systemic symptoms, the-area- underdisease-progress- curve (AUDPC), and rate of downy mildew development affected host resistance reactions. All components were significantly correlated. The adult plant resistant reaction was evident in resistant progenies showing prolonged onset of systemic symptoms. Transgressive segregation that exceeded the high and low parent values was also observed for all components of quantitative resistance to Philippine downy mildew.